Secondhand smoke exposure among young adults in a developing country – a Jordanian case - Haddad L; Abu Baker N; EL-Shahawy O; Al-Ali N; Shudayfat T (Dove Medical Press, 2013)
Linda Haddad,1 Nesrin Abu Baker,2 Omar El-Shahawy,3 Nahla Al-Ali,2 Tamadur Shudayfat,2 1Virginia Commonwealth University, School of Nursing and Institute for Drug and Alcohol Studies, Richmond, VA, USA; 2Jordan University of Science and Technology, School of Nursing, Irbid, Jordan; 3Social and Behavioral Health Department, School of Medicine, Virginia Commonwealth University, Richmond, VA, USA Abstract: Secondhand smoke (SHS) exposure is a potentially preventable environmental pollutant that remains a major global public health concern. A descriptive cross-sectional design was used to assess secondhand smoke exposure, knowledge, attitudes, and avoidance behaviors, as well as policy agreements related to SHS among young adult university students in the northern part of Jordan. A convenience sample of 800 university students from three public universities participated in the present study. They completed four questionnaires: the Sociodemographic Questionnaire, the Household SHS Exposure Questionnaire, the Knowledge and Attitudes Toward SHS Exposure Questionnaire, and the Avoidance of SHS Exposure Scale. Findings showed that SHS exposure among nonsmoking university students was 96%. In addition, the mean hours of exposure per day was 4.64 hours (standard deviation = 4.28), and the mean days of exposure per week was 5.14 days (standard deviation = 2.1). Based on the the students reported high hours of exposure, our results suggest that even though a student has knowledge of the dangers of SHS and suitable avoidance behaviors, he or she is unable to avoid SHS. Advocacy for effective interventions to avoid exposure to SHS should be initiated for Jordanian society as a whole. Keywords: secondhand smoking, college students, Jordan, exposure